محددات استثمارات القطاع العام - حالة الجزائر - - برحومة, عبد الحميد (Université de M'sila, 2009)
Despite the decreasing role of the public sector in the last decades in the economic development, and the concentration of its efforts towards the social aspects, it still has a large strategic investment projects in both the developed and developing countries. Through this paper we aim to give explanation to the determinants of public investment, which enables to understand more about the developing role of public projects in the different economic systems. Furthermore, and through this paper we will give insights on the behaviour of the Algerian Public Enterprises and the determinants of their projects since the beginning of the economic reforms in order to better apprehend the future of this sector.